Functional organization of the Golgi apparatus in glycosphingolipid biosynthesis: Lactosylceramide and subsequent glycosphingolipids are formed in the lumen of the late Golgi - Lannert, Heinrich; Gorgas, Karin; Meißner, Ingrid; Wieland, Felix T.; Jeckel, Dieter (The journal of biological chemistry, 1998)
Biosynthesis of plasma membrane sphingolipids involves the coordinate action of enzymes localized to individual compartments of the biosynthetic secretory pathway of proteins. These stations include the endoplasmic reticulum and the Golgi apparatus. Although a precise localization of all the enzymes that synthesize glycosphingolipids has not been achieved to date, it is assumed that the sequence of events in glycosphingolipid biosynthesis resembles that in glycoprotein biosynthesis, i.e. that early reactions occur in early stations (endoplasmic reticulum and cis/medial Golgi) of the pathway, and late reactions occur in late stations (trans Golgi/trans Golgi network). Using truncated analogues of ceramide and glucosylceramide that allow measurement of enzyme activities in intact membrane fractions, we have reinvestigated the localization of individual enzymes involved in glycosphingolipid biosynthesis and for the first time studied the localization of lactosylceramide synthase after partial separation of Golgi membranes as previously described (Trinchera, M., and Ghidoni, R. (1989) J. Biol. Chem. 264, 15766-15769). Here, we show that the reactions involved in higher glycosphingolipid biosynthesis, including lactosylceramide synthesis, all reside in the lumen of the late Golgi compartments from rat liver.
Artikelversion: 4. Januar 2021
Gesehen am 28.04.2025